The impact of domestic public debt on financial development in Malaysia - Mok, Wei Mun; Ismail, Normaz Wana (Macrothink Institute, 2015)
When the government heavily borrows domestically from the banking sector to finance its expenditures, there is possibility that public debt will lead to a crowding out effect on private investment since bank credit is a primary funding source for the private sector. This study examines the linkages between domestic public debt and financial development in Malaysia for the period of 1980 to 2010. Our analysis suggests that domestic public debt from banks has a negative relationship with financial development. Meanwhile, the crowding out effect is evident during the occurrence of financial crises.